"Why Couldn't a Bomb Have Hit Me?": Letters From a Jewish Woman in 1940s Vienna. Issue 3 (2nd September 2018) - Weinberger, Ruth Jolanda; Weinberger, Peter
ABSTRACT: In 1938, nearly 200, 000 Jews lived in Austria. Within four years, only about 7, 000 Jews remained. One of those 7, 000 was my grandmother, Rosa Weinberger. My grandfather was a non-Jewish resistance fighter, and together they had a son - my father, Peter - in 1943, born shortly after her family was transported to Auschwitz. My grandmother and my father survived the war hiding in Upper Austria, and eventually returned to postwar Vienna. But with her family gone, she was overwhelmed by feelings of grief, distrust and guilt. Lacking any societal support, and caught in the political turmoil of the time, she found relief only in written letters she exchanged with two surviving family members. Those letters are a rare account of daily life for Jews who were able to remain in Nazi territory, and who after the war struggled to rebuild their lives in a country deeply involved in the atrocities.